Comparative analysis of "Psyche" of young judo players from a big city and small towns - Janowska, Patrycja; Stępniak, Robert (Journal of Education, Health and Sport, 2018)
Aim: To provide judo coaches the info about some aspect of ‘Psycho’ of young judo adepts so it can be used in the training process. Materials and methods: The group of 31 young boys who practice judo in Bydgoszcz and the group of 27 boys who practice judo in small towns around Bydgoszcz were selected for the test. The so called ‘Brown Test’ by prof. W. Starosta of the Sport Way Academy was used. Results: There were significant differences observed in all measured values. Conclusion: The psychological ‘Brown test’ is an important source of information of children’s psychological predispositions.